2009
DOI: 10.1515/cclm.2009.212
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of matrix metalloproteinase-2 and -9 and conventional tumor markers (CEA and CA 19-9) in patients with colorectal and gastric cancers

Abstract: Background: Matrix metalloproteinases (MMPs), especially MMP-2 and MMP-9, play an important role in tumor invasion and metastasis. This study aimed to determine the serum levels of MMP-2, MMP-9, 130-and 225-kDa gelatinolytic bands and conventional tumor markers, carcinoembryonic antigen (CEA) and cancer antigen (CA) 19-9, in patients with gastrointestinal cancers. The relationship between these parameters and clinicopathological factors was also studied. Methods: Sera from controls (ns19), and patients with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…In a recent prospective study assessing MMP-2 and MMP-9 activity in serum samples of patients with CRC, those with gastric cancer, and controls, serum levels of MMP-9, but not MMP-2, were significantly higher in patients with CRC and gastric cancer than in controls [11]. By contrast, another study did not find any association between MMP-9 serum levels and the presence of CRC [12].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 87%
“…In a recent prospective study assessing MMP-2 and MMP-9 activity in serum samples of patients with CRC, those with gastric cancer, and controls, serum levels of MMP-9, but not MMP-2, were significantly higher in patients with CRC and gastric cancer than in controls [11]. By contrast, another study did not find any association between MMP-9 serum levels and the presence of CRC [12].…”
Section: Matrix Metalloproteinasesmentioning
confidence: 87%
“…Some data indicate that high circulating VEGF concentrations may predict the response to anti-VEGF therapy, e.g., bevacizumab [56] . Similarly, the determination of matrix metaloproteinases, enzymes that play an important role in tumor invasion and formation of metastases has been introduced [57] .…”
Section: Tumor Markers -The Old and The Newmentioning
confidence: 99%
“…Overexpression of the glycoprotein leads to inhibition of cell differentiation and disruption of cellular polarisation and tissue structure. It was observed that anoikis, an apoptotic process initiated when there is poor or no cell-ECM contact, is also downregulated by CEA overexpression (Lankiewicz et al, 2008;Emara et al, 2009).…”
Section: Metastasis-associated Factors Facilitating the Progression Omentioning
confidence: 99%